Some undecidable problems related to the Herbrand theorem - Gurevich, Yuri; Veanes, Margus (1997)
We improve upon a number of recent undecidability results related to the socalled Herbrand Skeleton Problem, the Simultaneous Rigid E-Unification Problem and the prenex fragment of intuitionistic logic with equality.